2019
DOI: 10.1111/ppc.12431
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence from social media use, subjective well‐being, stress, and loneliness

Abstract: Purpose: Studies with experimental designs in which the association between participants’ subjective well‐being and their use of social media is studied remain rare. This study tested the effect of abstaining from social media use on participants’ well‐being, affect, perceived stress, and sense of perceived loneliness. Design and Methods: Randomized, controlled design. Sixty‐eight participants were randomized to one of two conditions. Findings: Those who abstained from social media use, compared with those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 56 publications
1
52
1
1
Order By: Relevance
“…12 Moreover, evidence from cohort research has also supported that binge-watching could be associated with stress. 8 The results of hypothesis 3 are consistent with the past research suggesting emergent psychological issues such as loneliness owing to the addictive use of digital technologies.- 42,45 These addictive behaviors among the binge-watchers isolate the individuals from their real-life situations and align them more with the realities of binge-watching. As a result, the individuals feel a sense of loneliness when their real-life realities and mediated realities are incompatible.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…12 Moreover, evidence from cohort research has also supported that binge-watching could be associated with stress. 8 The results of hypothesis 3 are consistent with the past research suggesting emergent psychological issues such as loneliness owing to the addictive use of digital technologies.- 42,45 These addictive behaviors among the binge-watchers isolate the individuals from their real-life situations and align them more with the realities of binge-watching. As a result, the individuals feel a sense of loneliness when their real-life realities and mediated realities are incompatible.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have identified the association between the growing addictive use of digital technologies and increases in the level of loneliness. 42,45 Therefore, presumably, people may experience feelings that include a sense of loss, longing for more, melancholy, and feelings of emptiness and frustration after watching multiple series. Based on this empirical evidence, we hypothesize that; H3.…”
Section: Binge-watching and Lonelinessmentioning
confidence: 99%
“…On the individual side, frequent or passive users may benefit from cessation, as a 1-week break from Facebook increased these users' life satisfaction and positive emotions (Tromholt, 2016). However, other research has found that short periods of abstinence have no effect (e.g., Agadullina et al, 2020;Hall et al, 2019) or have negative effects such as increased loneliness and decreased life satisfaction (Vally & D'Souza, 2019;Vanman et al, 2018). The habit-forming nature of social media may thus, like most habits, yield a range of costs and benefits.…”
Section: Summary and Con Clus I Onmentioning
confidence: 99%
“…For instance, Hall et al (40) manipulated social media use by randomly assigning undergraduates to varying durations of abstinence (0, 2, 3, and 4 weeks) and found that social media abstention did not account for changes in loneliness or subjective well-being [see (41) for similar finding]. Moreover, Vally and D'Souza (42) showed that a week-long abstinence from social media led to reduced life satisfaction and increased negative affect and perceived stress.…”
Section: Experimental Findingsmentioning
confidence: 99%